Діарилетеновмісні "степлені” пептиди – інгібітори p53/MDM2 взаємодії - Баканович, Ю.В.; Стрижак, О.В.; Комаров, І.В.; Хиля, В.П. (Доповіді НАН України, 2020)
Проведено дизайн, синтез та дослідження як інгібіторів p53/MDM2 взаємодії шести нових “степлених” фотоконтрольованих пептидоміметиків — аналогів відомого інгібітора pDI. Фотоконтролю активності пептидоміметиків досягнуто завдяки введенню в їх молекули фрагмента діарилетену, здатного до фотоізомеризації. Встановлено, що з'єднання амінокислотних залишків у лінійному прекурсорі в положеннях
i,i+7 діарилетеновмісним лінкером є оптимальним для отримання активних фотоконтрольованих інгібіторів. Константи інгібування протеїну MDM2 деяких отриманих пептидоміметиків сягали значень кількох наномолів, що ставить їх в один ряд з найбільш активними відомими на цей час інгібіторами p53/MDM2
взаємодії. Перспективним є подальше дослідження отриманих сполук як засобів терапії захворювань на рак. Interaction between p53 and the E3 ubiquitin ligase murine double minute 2 homolog (MDM2) is regarded
as an important target for anticancer therapeutics. The p53/MDM2 protein-protein interaction is one of the
best-studied and most targeted intracellular processes related to cancer progression. Toxicity associated with
p53 activation has been reported as a critical issue; therefore, the search for novel selective modulators of this
pro tein-protein interaction is of great interest. In this work, the design, synthesis, and study, as the p53/MDM2
interaction inhibitors, of six new “stapled” photocontrolled peptidomimetics — analogues of the known inhibitor
pDI — are reported. Photocontrol of peptidomimetic activity was achieved by introducing a photoisomerizable
diarylethene fragment into their molecules. Six peptidomimetics bearing the diarylethene group cross-linking
amino acid side chains in different positions of the polypeptide strand: (i,i+4), (i,i+7), (i,i+11) were prepared.
The stapling was achieved using the Cu-catalyzed “click”-reaction between the diarylethene-based bis-alkynes
and two azidoornithine residues placed in appropriate positions of the linear peptide precursors. All the compounds
were obtained with the diarylethene moiety in the so-called “open” conformation which can be generated
by visible light. They were purified by high performance liquid chromatography. It has been found that the stapling
of amino acid residues at positions (i,i+7) in the linear precursor with the diarylethene linker is optimal for
obtaining active photocontrolled inhibitors, in terms of the yields of the stapling reaction. Attempts at (i,i+4)
and (i,i+11) stapling gave either no product or the compounds, where the diarylethene building block reacted
with the peptide precursor through only one alkyne group. The values of the inhibition constants for some of
the obtained peptidomimetics measured with the use of a fluorescence polarization assay reached several nanomoles,
which puts the obtained peptidomimetics in line with the most active inhibitors of the p53/MDM2
interaction known at the time. Further studies of the obtained compounds as possible candidates for the cancer
photopharmacology are warranted.